What do cooperative firms maximize, if at all? Evidence from Emilia-Romagna in the pre-Covid decade - Guido Caselli; Michele Costa; Flavio Delbono (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2021)
The Italian region Emilia-Romagna ranks first among the world's most important cooperative districts. Using a unique dataset covering all firms registered in the region, we investigate the performance of active firms in the period 2010-18. By focusing on employment, revenue and profits of cooperative firms as compared to conventional firms, we disentangle the differences between the average performance of the two types of companies and detect the presence of a "size effect" driving much of the difference between them. Moreover, our results strengthen previous empirical evidence about the countercyclical role of cooperative firms: they seem to optimize a mixture of employment and profits, assigning a greater weight to the former during downturns and stagnation. Finally, we examine the regional logistics industry and compare also the profitability of employees in the two segments of the sector.
Keywords: L21; L25; 330; cooperative firms; employment; Gini decomposition